Effects of flunixin meglumine administration on physiological and performance responses of transported feeder cattle - Cooke, Reinaldo Fernandes [UNESP]; Cappellozza, B. I.; Guarnieri Filho, T. A. [UNESP]; Bohnert, D. W. (Amer Soc Animal Science, 2013)
The objective was to evaluate the effects of flunixin meglumine administration on physiological and performance responses of transported cattle during feedlot receiving. Forty-five Angus x Hereford steers were ranked by BW on d 0 and assigned to 1 of 3 treatments:1) transport for 1,280 km in a commercial livestock trailer and administration of flunixin meglumine (1.1 mg/kg BW; intravenous) at loading (d 0) and unloading (d 1; FM), 2) transport for 1,280 km in a commercial livestock trailer and administration of 0.9% saline (0.022 mL/kg BW; intravenous) at loading (d 0) and unloading (d 1; TRANS), or 3) no transport and administration of 0.9% saline (0.022 mL/kg BW; intravenous) concurrently with loading (d 0) and unloading (d 1) of FM and TRANS cohorts (CON). Upon arrival and processing for treatment administration on d 1, steers within each treatment were ranked by BW and assigned to 15 feedlot pens (5 pens/treatment, 3 steers/pen). Full BW was recorded before (d -1 and 0) treatment application and at the end of experiment (d 28 and 29) for ADG calculation. Total DMI was evaluated daily from d 1 to 28. Blood samples were collected on d 0 (before treatment administration), 1 (after unloading but before treatment administration), 4, 7, 10, 14, 21, and 28. Body weight shrink from d 0 to 1 was less (P < 0.01) in CON vs. FM and TRANS but similar (P = 0.94) between TRANS and FM. Mean ADG was greater (P <= 0.04) in CON vs. FM and TRANS but similar (P = 0.69) between TRANS and FM. No treatment effects were detected on DMI, but CON had greater G:F vs. TRANS (P = 0.08) and FM (P = 0.02), whereas G:F was similar (P = 0.68) between TRANS and FM. Mean plasma cortisol concentrations tended (P <= 0.09) to be greater in TRANS vs. FM and CON but was similar (P = 0.87) between CON and FM. Plasma NEFA concentrations were greater (P <= 0.02) for TRANS and FM vs. CON on d 1 and greater (P <= 0.04) for FM vs. TRANS and CON on d 4. Plasma ceruloplasmin concentrations were greater (P <= 0.03) for TRANS vs. CON on d 1, 4, and 7, greater (P <= 0.05) for TRANS vs. FM on d 4 and 7, and greater (P <= 0.04) for FM vs. CON on d 1 and 4. Plasma haptoglobin concentrations were greater (P < 0.01) for TRANS vs. CON and FM on d 1 and 4 and greater (P <= 0.05) for FM vs. CON on d 1 and 4. In conclusion, flunixin meglumine reduced the cortisol and acute-phase protein responses elicited by road transport but did not improve receiving performance of feeder cattle.
Keywords: acute-phase proteins; beef cattle; feedlot receiving; flunixin meglumine; transport